Active Multifunctional Microelectromechanical System Metadevices: Applications in Polarization Control, Wavefront Deflection, and Holograms. Issue 2 (28th November 2016) - Cong, Longqing; Pitchappa, Prakash; Wu, Yang; Ke, Lin; Lee, Chengkuo; Singh, Navab; Yang, Hyunsoo; Singh, Ranjan
Abstract : Metasurfaces have provided a novel route to control the local phase of electromagnetic radiation through subwavelength scatterers where the properties of each element remain passive. A passive metasurface design can only achieve a specific functionality as it is extremely challenging to reconfigure each element that contributes toward the control of the radiation. In this work, the authors propose a different scheme based on microelectromechanical system (MEMS) to reconfigure the resonance and radiation phase via control of each dipolar element. The suspension angle of the individual bimorph cantilever in air can be precisely controlled through electrostatic actuation that determines the operative phase diagram of the metadevice. The dynamic polarization conversion is demonstrated through global control. In addition, it is proposed that a multifunctional operation such as dynamic wavefront deflection and rewritable holographic display can be accomplished by using 1D and 2D control of the cantilever array when each cantilever in the MEMS metadevice array is uniformly and accurately controlled in the large‐area samples. Such a rewritable proposition can enable myriad of applications of MEMS‐based metadevices in polarization‐division multiplexing and dynamic flat lenses. Abstract : The microelectromechanical system (MEMS)‐based metadevice provides the freedom to encode at the unit cell level. A multifunctional MEMS metadevice is proposed for active polarization conversion, dynamic wavefront deflection, and real‐time rewritable holographic displays.